EXPLORING WORK PLACEMENT EXPERIENCE: CASE OF THE UNIVERSITY OF TECHNOLOGY, MAURITIUS: Received: 1st June, 2021; Revised: 28th October, 2021; 19th January, 2022; Accepted: 09th February, 2022 - Odit-Dookhan, Kiran; Chittoo, Hemant Birandranath; Armoogum, Vinaye; Odit, Mohun Prasadsing; Seebaluck, Vanessa; Narsoo, J (PEOPLE: International Journal of Social Sciences, 2022)
The inclusion of job training and learning has recently been acknowledged as not only a key element of organizational initiatives to enhance learners’ job readiness, but even as an organizational initiative to establish themselves in the marketable global education industry (Tran & Soejatminah, 2016). University students’ work-readiness continue to be a significant issue, with Mauritian industries lamenting a lack of soft skills and real-life experiences deemed necessary for recruitment. The University of Technology, Mauritius (UTM) has completely adopted the Work Placement principles since 2014 to extend numerous options to its learners to offer relevant work experiences. The present study aims at exploring the role of the Work Placement experience among the students studying at the UTM. A survey was conducted using an online questionnaire among 230 participants to measure soft-skill development. Before and after the internship, descriptive statistics such as means, standard deviations, and varying scores were investigated using SPSS. The results reveal that students have a positive attitude toward the acquired skills and abilities through Work Placement. The majority of the students asserted that through their Work Placement experiences, they have acquired important soft skills and have become excellent team players and good communicators.